Surface quality of furniture components using a band saw, milling machine, and two species (Revista de Ciências Agroveterinárias, 2021)
This study is dedicated to considering the use of eucalyptus and Ocotea porosa to produce classic-style furniture, assessing the machining time and surface quality. For such, the survey of data on the surface quality of eucalyptus and Ocotea porosa pieces was carried out through a visual assessment with the adaptation of the methodology described in standard ASTM 1666. This analysis of the wood surface quality occurred using two different species and two machining modalities (a band saw and a copy milling machine) for parts intended to produce components (feet) for classic furniture. After making the feet, the pieces of furniture were assembled and reassessed. Forty samples were selected and evaluated for initial defects through visual inspection, and the non-parametric Kruskal-Wallis statistical test was applied. The values found for surface quality were considered good quality, with more time being necessary to perform the finishing of the parts processed with the band saw than the milling machine. One may conclude that the milling time spent on each treatment influences the production capacity of the company, with the cuts carried out with the milling machine being faster and with better surface finishing.
Keywords: machining; non-parametric analysis; surface finish